PERANCANGAN MEDIA PROMOSI WOMANTALK.COM SEBAGAI MEDIA INFORMASI PEREMPUAN INDONESIA - Zahrowi, Muhamad Imam; Wardhani, Ariani Kusumo (Anggada : Jurnal Desain dan Seni, 2020)
The visual role in promotion is needed in all fields of life. Visuals in promotion influence by a form that describes and differentiates a brand. Differentiate brands or differentiate one brand from other competitors' brands so that the comparison can be seen and felt prominently in order to be remembered by the public. Digital media news portals for women use promotions that have been started from digital media and spread to social media that is easy to reach for all Indonesian people. The purpose of this design is to provide a new visual that can later be used to promote the women's news portal Womantalk.com so that it can be more enjoyed by readers in various circles on social media. For this reason, the method used in this design is to make promotions on social media Instagram with illustrations as explanatory media in the delivery of information delivered.